LIKUIDITAS, AKTIVITAS, DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN AUTOMOTIVE YANG TERDAFTAR DI BEI - Rizka Chairunnisa (E-Mabis: Jurnal Ekonomi Manajemen dan Bisnis, 2019)
The purpose of this study was to determine the significant influence Current Ratio, Accounts Receivable Turnover and Return On Asset Share Price Automotive Company Listed on the Indonesian Stock Exchange. The analysis used in this research is multiple linear regression analysis. The hypothesis is suspected the influence of Current Ratio, ROA, INTO on stock prices of components in the automotive sector and the stock exchange Indonesia 2011-2013. F-test analysis results, there is a relationship that is of influence between the Current Ratio, ROA, INTO simultaneously to the stock price in the automotive sector listed in  Indonesia stock exchange 2011-2013. T test results showed ROA Inventory Turnover and partially influence on stock prices of automotive and components sector in Indonesia Stock Exchange. The coefficient of determination (R2 = 0.245 or 24.5%), which means that independent variables (Current Ratio, ROA, INTO) can only explain 24.5% of the value of the company and 75.5% are influenced by other factors.